A lesson for the future of our science : my testimony on Lord Patrick M.S. Blackett - Zichichi, Antonino (2016)
"This unique volume contains a tribute to Lord Patrick M.S. Blackett through the testimony of Professor Antonino Zichichi, who was one of Blackett's pupils in the experiment at the Sphinx Observatory, Europe's highest lab (3,580 meters a.s.l.), at Jungfraujoch.The book presents an overview of Blackett's most significant discoveries, such as the so called "vacuum polarization" effect, the first example of "virtual physics", and the "strange particles", that opened a new horizon towards the existence of the subnuclear universe. After discussing the profound implications of Blackett's pioneering contributions to Subnuclear Physics, the book also recalls his deep interest in the promotion of scientific culture. Blackett was firmly convinced that physicists must be engaged directly to let the people outside our labs know what the role of science is in the progress of our civilisation. In particular, according to Blackett and his friend Bertrand Russell, the Manhattan Project was the example of how the new frontiers of science and technology would have been implemented in the future. In this respect, the role of dedicated institutions is discussed, as a new bridge between traditional university teaching and the big projects for the future of science and technology"--
Includes bibliographical references and indexes.
Keywords: Blackett, P. M. S. -- Baron Blackett, -- 1897-1974.; Physicists -- Great Britain -- Biography; Creative ability in science; Particles (Nuclear physics); Vacuum polarization; World War, 1939-1945 -- Science